Analysis of dynamic viscosity via experiment and empirical correlation through response surface methodology (rsm) for cellulose nanocrystal (cnc) dispersed in ethylene glycol- water mixture - D., Ramasamy; K., Kadirgama; Neshabran, Ramachandran; W. H., Azmi (2018)
Heat-transfer improvement is a vital challenge in thermal engineering. Due to their vast application in the thermal energy transfer, the researchers have found a latest method in enhancing the heat transfer performance by using nanofluid. Dispersion of nanosubstance not only enhances thermal conductivity but dynamic viscosity too. Viscosity enhancement is vital parameter that must be studied for the application purposes. It increases power consumption which reduces pump performance.